2005
DOI: 10.1063/1.2107307
|View full text |Cite
|
Sign up to set email alerts
|

Nilpotent representations of classical quantum groups at roots of unity

Abstract: Properly specializing the parameters in ``Schnizer modules'', for type A,B,C and D, we get its unique primitive vector. Then we show that the module generated by the primitive vector is an irreducible highest weight module of finite dimensional classical quantum groups at roots of unity.Comment: 29 pages, new section added and some proof revise

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2006
2006
2007
2007

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…For any λ ∈ Z n l , there exists a unique (up to isomorphic) finite dimensional irreducible nilpotent U ε (g)-module L nil ε (λ) of type 1 with highest weight λ. Conversely, if L is a finite dimensional irreducible nilpotent U ε (g)-module of type 1, then there exists a λ ∈ Z n l such that L is isomorphic to L nil ε (λ). By the similar manner to the proof of Theorem 5.5(ii) in [8] or Theorem 4.10 in [1], we obtain the following proposition.…”
Section: Quantum Algebras At Roots Of Unitymentioning
confidence: 61%
See 3 more Smart Citations
“…For any λ ∈ Z n l , there exists a unique (up to isomorphic) finite dimensional irreducible nilpotent U ε (g)-module L nil ε (λ) of type 1 with highest weight λ. Conversely, if L is a finite dimensional irreducible nilpotent U ε (g)-module of type 1, then there exists a λ ∈ Z n l such that L is isomorphic to L nil ε (λ). By the similar manner to the proof of Theorem 5.5(ii) in [8] or Theorem 4.10 in [1], we obtain the following proposition.…”
Section: Quantum Algebras At Roots Of Unitymentioning
confidence: 61%
“…Then we can construct finite dimensional irreducible nilpotent U ε (g)-modules of type 1 with highest weight (0, · · · , 0, λ k , · · · , λ n ) as a submodule of a l (Nn−N k−1 ) -dimensional U ε (g)-module, where N n is the number of the positive roots of g and n is the rank of g. In particular, these results cover the ones of [1].…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations
“…showed that one can construct V nil ε (λ) as the subrepresentation of a maximal cyclic representation by specializing their parameters properly for type A. Similarly, in [1], we found that we can construct V nil ε (λ) as a submodule of a Schnizer module if g=A, B, C or D, and then we can construct V nil ε (λ) ± a as the submodule of evaluation of a Schnizer module. By using this fact, we can prove (2) (see §5 alternative proof of Proposition 5.11 (b)).…”
Section: Introductionmentioning
confidence: 85%